Use of blood lactate measurements for prediction of exercise performance and for control of training. Recommendations for long-distance running - Billat, L. V. (Sports Medicine, 1996)
Time over a distance, i.e. speed, is the reference for performance for all events whose rules are based on locomotion in different mechanical constraints. A certain power output has to be maintained during a distance or over time. The energy requirements and metabolic support for optimal performance are functions of the length of the race and the intensity at which it is completed. However, despite the complexity of the regulation of lactate metabolism, blood lactate measurements can be used by coaches for prediction of exercise performance. The anaerobic threshold, commonly defined as the exercise intensity, speed or fraction of maximal oxygen uptake (VO2max) at a fixed blood lactate level or at a maximal lactate steady-state (MLSS), has been accepted as a measure of the endurance. The blood lactate threshold, expressed as a fraction of the velocity associated with VO2max, depends on the relationship between velocity and oxygen uptake (VO2). The measurement of the post-competition blood lactate in short events (lasting 1 to 2 minutes) has been found to be related to the performance in events (400 to 800m in running). Blood lactate levels can be used to assist with determining training exercise intensity. However, to interpret the training effect on the blood lactate profile, the athlete's nutritional state and exercise protocol have also to be controlled. Moreover, improvement of fractional utilisation of VO2max at the MLSS has to be considered among all discriminating factors of the performance, such as the velocity associated with VO2max.